Theory and Methods of Quantification Design on System-Level Electromagnetic Compatibility - Su, Donglin; Xie, Shuguo; Dai, Fei.; Liu, Yan.; Jia, Yunfeng; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book systematically explains the fundamentals of system-level electromagnetic compatibility and introduces the basic concept of system-level electromagnetic compatibility quantification design. The topics covered include the critical technologies in the top-down quantification design of electromagnetic compatibility, quantification design of system-level electromagnetic compatibility, evaluation methods and application examples, quality control and application examples of electromagnetic compatibility development process, and real-world engineering example analysis of electromagnetic compatibility. The book proposes a top-down system-level electromagnetic compatibility quantification design method and is the first book to describe in detail how to quantitatively evaluate and predict system-level electromagnetic compatibility performance. It includes abundant engineering examples and experimental data demonstrating the usage and results of the top-down quantification design methods of system-level electromagnetic compatibility. It enables readers to obtain a thorough understanding of the theory and methods of system-level electromagnetic compatibility quantification design as well as the methodologies for engineering practice.
Electromagnetic Field and Wave -- Microwave Technology -- Antenna Theory and Engineering -- Basic Concepts of Quantification System-Level EMC Design -- Critical Techniques of Quantification System-Level EMC Design -- Cases of System-Level Quantification Design and Evaluation -- EMC Evaluation and Quality Control Methodologies -- EMC Engineering Case Analyses -- Appendix A Software platform Descriptions for Quantification System-Level EMC Design -- Appendix B Software for Aircraft EMC Evaluation in Different Phases -- Appendix C Software for Aircraft EMC Management.
Keywords: Telecommunication; Electronic circuits; Electrodynamics; Microwaves, RF Engineering and Optical Communications; Electronic Circuits and Systems; Classical Electrodynamics